(untitled) (Journal of Engineering, 2002)
Rotating turbine blades are the important parts in gas turbines. Hence, an accurate estimation of stresses, deformations and vibration characteristics are required in the design to avoid failure and obtain an optimum weight and cost. Because in recent years interest in the effect of temperature on solid bodies has greatly increased, thremal effects are investigated in addition to the rotation of effects. This work presents the numerical solutions of the blade using degenerated curved shell theory, finite element package has been developed using the degenerated curved shell element as a discretization element in order to obtain the stresses, deformations and vibration characteristics of the rotating blades. The numerical results are compared with experimental and theoretical results :n the published literature and they showed good agreement.